A STUDY TO ASSESS CHANGE IN CONTRAST SENSITIVITY AND VISUAL ACUITY IN PROLIFERATIVE DIABETIC RETINOPATHY PATIENTS UNDERGOING ANTI-VEGF TREATMENT AND ROLE OF LOW VISION AID IN SUCH PATIENTS - YADAV, VISHAL; SACHDEVA, LALIT; SRIVASTAVA, ANIL KUMAR; BHUSHAN, PRASHANT (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The aim of this study was to study the effect of intravitreal anti-vascular endothelial growth factor (VEGF) on the visual acuity (VA) using logMAR charts and the contrast sensitivity (CS) using the pelli-robson chart in patients of advanced diabetic retinopathy. Design: We performed a retrospective study to assess the change in CS and VA in diabetic retinopathy (DR) with or without proliferative DR patients receiving intra-vitreal anti VEGF. Methods: The study was done at our institution where 40 patients of DR were included in the study, 20 cases (20 eyes) and 20 controls (20 eyes). Moreover, it comes under the criteria of low vision and above 18 years of age and VA >6/60. VA and CS were compared before injection and after injection at 14 days, 30 days, and 90 days, respectively. Results: On comparing the mean of CS change before injections and after injections at 14 days (p=0.036), 30 days (p=0.012), and 90 days (p=0.012), respectively, showed a significant association between change in CS change within group but on comparing with control group at 14 days (p=0.195), 30 days (p=0.247), 90 days (p=0.247), respectively, showed no significant association. Another comparison of mean VA before injection and after injection in the case group at 14 days, 30 days, and 90 days, respectively, (p=0.329) remains the same. Which is insignificant but on comparison with the control group (p=0.02) showed a significant association. Conclusion: Whatever VA and CS are achieved with anti-VEGF was completed at 14 days of injection.